Identification of psoriatic arthritis in patients with psoriasis - Coates, LC; Eder, L; Poddubnyy, D; Rosen, CF (Journal of Rheumatology, 2023)
People with psoriasis are at increased risk of developing psoriatic arthritis. Screening patients with psoriasis for psoriatic arthritis may be helpful in diagnosing psoriatic arthritis early. Dermatologists play a role in assessing their patients with psoriasis for musculoskeletal symptoms and referring them to rheumatologist for diagnosis and treatment.